Anion-induced palladium nanoparticle formation during the on-surface growth of molecular assemblies. Issue 13 (24th December 2015) - Morozov, Michael; Bendikov, Tatyana; Evmenenko, Guennadi; Dutta, Pulak; Lahav, Michal; van der Boom, Milko E.
Abstract : We demonstrate a process that results in the formation of palladium nanoparticles during the assembly of molecular thin films. Abstract : We demonstrate a process that results in the formation of palladium nanoparticles during the assembly of molecular thin films. These nanoparticles are embedded in the films and are generated by a chemical reaction of the counter anions of the molecular components with the metal salt that is used for cross-linking these components.